Weight Optimization in Enhanced Multivariance Product Representation (EMPR) Method - (:unkn) unknown (AMER INST PHYSICS, 2010)
This paper focuses on the weight function optimization in Enhanced Multivariance Product Representation (EMPR) via constancy maximization. This is done by tracing the same philosophy as HDMR weight function optimization.
Keywords: High Dimensional Model Representation; Enhanced Multivariance Product Representation; Optimization; Multivariate Functions; Support Functions; Weight Functions